Assessing the nutritional quality of Pleurotus ostreatus (oyster mushroom) - Effiong, Magdalene Eno; Umeokwochi, Chidinma Precious; Afolabi, Israel Sunmola; Chinedu, Shalom Nwodo (Frontiers in Nutrition, 2024)
There is a huge gap between food production and the exploding population demands in various parts of the world, especially developing countries. This increases the chances of malnutrition, leading to increased disease incidence and the need for functional foods to reduce mortality. Pleurotus ostreatus are edible mushrooms that are cheaply sourced and rich in nutrient with the potential to be harnessed towards addressing the present and future food crisis while serving as functional foods for disease prevention and treatment. This study evaluated the nutritional, proximate, vitamins and amino acids contents of Pleurotus ostreatus. The proximate composition of Pleurotus ostreatus in this study revealed that it contains 43.42% carbohydrate, 23.63% crude fiber, 17.06% crude protein, 8.22% ash, 1.21% lipid and a moisture content of 91.01% and 6.46% for fresh and dry samples of Pleurotus ostreatus respectively. The monosaccharide and disaccharide profile of Pleurotus ostreatus revealed the presence of glucose (55.08g/100g), xylose (7.19g/100g), fructose (19.70g/100g), galactose (17.47g/100g), trehalose (7.37g/100g), chitobiose (11.79g/100g), maltose (29.21g/100g), sucrose (51.60g/100g) and lower amounts of cellobiose (0.01g/100g), erythrose (0.48g/100g) and other unidentified sugars. Potassium, Iron and Magnesium were the highest minerals present with 12.25mg, 9.66mg and 7.00mg amounts respectively. The vitamin profile revealed the presence of vitamin A (2.93 IU/100g), C (16.46mg/100g), E (21.50mg/100g) and B vitamins with vitamin B2 having the highest concentration of 92.97mg/kg. The amino acid scores showed that Pleurotus ostreatus had more non-essential amino acids (564.17mg/100g) than essential amino acids (67.83mg/100g) with a ratio of 0.11. Lysine (23.18mg/100g) was the highest essential amino acid while aspartic acid (492.12mg/kg) was the highest non-essential amino acid present in Pleurotus ostreatus. It had a higher concentration of acidic amino acids, 492.12mg/100g (77.87%), followed by neutral amino acids, 106.66mg/100g (16.88%) and least were the basic amino acids, 23.18mg/100g (3.67%). Based on the nutritional assessment of the Pleurotus ostreatus analyzed in this study, it can be concluded that it can serve as an important functional food source that can be exploited to meet the increasing food demands and reduce micronutrient deficiencies in many parts of the world, especially developing countries.